Prediksi Jumlah Kunjungan Wisatawan Mancanegara Ke Indonesia Menggunakan Metode Average-Based Fuzzy Time Series Models - Teri Kincowati; Muhammad Tanzil Furqon; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia is a country that has a great diversity of cultures and natural wealth. One of Indonesia's natural wealth that is the attraction of the world is its tourist attractions. The beauty of tourist attractions in Indonesia makes Indonesia becomes a country that is often visited by foreign tourists on vacation. Tourism is one business that can increase economic growth. Tourists visit is increased sigficantly due to many factors, including competitive travel costs, promotion strategies that continue to be intensified, and many adequate travel routes. This must be balanced with adequate facilities and guaranteed security. The number of visitors that cannot be ascertained must be predictable in anticipation of sudden increases or deterioration, so that the state can determine policies towards changes in the number of visitors in the future. The method that will be used to predict in this study is the average-based fuzzy time series models and the using 216 data obtained from the official website of the Statistic Indonesia, it is data of the number of foreign tourist visits to Indonesia in the period January 1999 to December 2016. Based on the result of the study obtained MAPE value is 10,140%, that MAPE value is good to predict, because it is under 20%. So can be concluded that average-based fuzzy time series is good enough to predict the number of foreign tourists visit to Indonesia.